Component Reliability Prediction Model for Malaysia Offshore Regions Static and Regression Analysis - Kurian, V.J. (2013)
Abstract—Majority of the fixed jacket platforms installed in Malaysia water regions had already exceeded their design life. In order to prolong the service life of these aged platforms, their current structural integrity conditions need to be reviewed. System reliability governs the reliability of a structure. However, a system is consisted of many components. Combination of individual (component) reliability in dominant failure path(s) explains the system reliability. As oppose to the system reliability assessment method, generation of component reliability is much simpler. This paper presents the methodology for computing a simplified component reliability model. Interpolation methods for obtaining the met-ocean design values at different return periods are discussed. Also, effects of different met-ocean combinations are studied. Keywords—component reliability; met-ocean; interpolation